Superoxide is the critical driver of DOPAL autoxidation, lysyl adduct formation, and crosslinking of α-synuclein - Werner-Allen, Jon W. (Biochem Biophys Res Commun, 2017)
Parkinson’s disease has long been associated with redox imbalance and oxidative stress in dopaminergic neurons. The catecholaldehyde hypothesis proposes that 3,4-dihydroxyphenylacetaldehyde (DOPAL), an obligate product of dopamine catabolism, is a central nexus in a network of pathways leading to disease-state neurodegeneration, owing to its toxicity and potent ability to oligomerize α-synuclein, the main component of protein aggregates in Lewy bodies. In this work we examine the connection between reactive oxygen species and DOPAL autoxidation. We show that superoxide propagates a chain reaction oxidation, and that this reaction is dramatically inhibited by superoxide dismutase. Moreover, superoxide dismutase prevents DOPAL from forming dicatechol pyrrole adducts with lysine and from covalently crosslinking α-synuclein. Given that superoxide is a major radical byproduct of impaired cellular respiration, our results provide a possible mechanistic link between mitochondrial dysfunction and synuclein aggregation in dopaminergic neurons.